Vanishing Voices: Saving Languages Before it’s Too Late - Muhammad Ridwan; Belay Sitotaw Goshu (BIRCU, 2025)
The global decline of linguistic diversity threatens cultural heritage, with intergenerational language transmission increasingly reliant on education and digital tools amid urbanization and technological advancement. This study explores how education and digital tools influence transmission success across generations. Using modeling data for 50 initiatives, the study employs descriptive statistics, bar plots, scatter plots with regression, correlation heatmaps, and linear regression to analyze education level, digital tool usage, young speaker percentage, and transmission success. Education shows a modest positive impact (β = 0.0068, M = 0.53 for high-education initiatives), while digital tools exhibit a surprising negative effect (β = -0.1267, r = -0.41), with variability in outcomes. Young speakers’ proportion negatively correlates with success (β = -0.0558, r = -0.18), suggesting generational disconnects. Education supports transmission, but digital tools’ over-reliance may hinder success unless culturally integrated, highlighting the need for balanced strategies. Governments should fund immersion schools, NGOs should co-design digital tools with communities, and local groups should promote intergenerational activities.